Customer engagement in online social media platforms for small and medium eneterprise - Nazanin Roozegar, 1987- author; Nor Hidayati Zakaria, supervisor; Fakulti Komputeran (2013)
Thesis (Sarjana Sains (Teknologi Maklumat - Pengurusan)) - Universiti Teknologi Malaysia, 2013